Spatial based Land use Analysis in an Effort to Improve Environmental Quality in The Surakarta City Area - Layla Qodri Ani; Amanda Khoirun Nisa; Amanda Gheanisa Lutfi; Bhayangkara Satryo Wibowo; Fayza Ritalia (Universitas Muhammadiyah Surakarta, 2024)
This article discusses spatial-based land use analysis as a strategy to improve environmental quality in the Surakarta City Region. Surakarta City, like many cities in Indonesia, faces challenges in efficient and sustainable land management. This research aims to identify the potential for optimal land use in the context of urban spatial planning with a focus on environmental quality aspects. Spatial analysis and geographic modeling methods were used to evaluate existing land use and identify potential land conversions that could improve environmental quality. The results of this study include recommendations for land development strategies that can reduce negative impacts on the environment, such as uncontrolled urbanization, environmental degradation, and increased disaster risk. The article also highlights the importance of sustainable spatial planning in maintaining the city's ecosystem and ensuring that good environmental quality is maintained. The results of this study are expected to serve as a guide for authorities and decision makers in their efforts to improve environmental quality in Surakarta City Region and other similar cities in Indonesia.